Indices to Economic Texts from the Palace of Zimri-Lim (ca. 1782-1759 B.C.) - Kerestes, Terrence Michael (1982)
Ph.D. Dissertation; Chairman: George E. Mendenhall. Order No. DA8215027, cf. DissAbstr 43/02 (August 1982) 515-A.